Dietary Nutrition and Gut Microbiota Composition in Patients With Hypertensive Disorders of Pregnancy - Yu, Jinran; Zhang, Bo; Miao, Tingting; Hu, Haiting; Sun, Yongye (Frontiers in Nutrition, 2022)
Objective: The aim is to explore the intakes of dietary nutrient and the changes of gut microbiota composition among patients with hypertensive disorders of pregnancy (HDP), and provide theoretical basis for the prevention and treatment of HDP. Methods: This study was conducted at Maternal and Child Health Care Hospital of Changzhou. A total of 170 pregnant women (72 HDP patients in the case group and 98 healthy pregnant women in the control group) in the third trimester were enrolled. Dietary nutrient intakes were assessed through food frequency questionnaire survey. Fresh fecal samples were aseptically collected, and 16S rDNA sequencing was conducted. The intakes of dietary nutrient, and the diversity and relative abundance of gut microbiota were compared between pregnant women with and without HDP. Logistic regression model was used to investigate the association between differential gut microbial genera and the risk of HDP. Results: The daily dietary intakes of vitamin A and vitamin C in HDP pregnant women were significantly lower than those in the control group. The relative abundances of Bacteroidota, Bacteroidaceae, and Bacteroides were increased, and the relative abundances of Actinobacteriota, Lachnospiraceae, Prevotellaceae, Bifidobacteriaceae, Blautia, Prevotella, and Bifidobacterium were decreased in HDP women compared with those in the controls. In addition, the relative abundance of Bifidobacterium was positively correlated with dietary intakes of vitamin C and vitamin E in patients with HDP. After adjustment for confounding factors, the odds ratio (95% confidence interval) of HDP for the relative abundance of Bifidobacterium was 0.899 (0.813, 0.995). Conclusion: The composition of gut microbiota in HDP pregnant women was significantly changed compared with that of healthy controls. The relative abundance of Bifidobacterium was negatively associated with HDP. Moreover, dietary vitamin C and gut Bifidobacterium may cooperatively contribute to reduce the risk of HDP.